Notice of the first concert of the Musical Fund Society of Philadelphia, (United States; National Gazette and Literary Register; Philadelphia, 2020)
Notice in the National Gazette and Literary Register, April 23, 1821 (vol. 1 no. 147), page 3, column 4, on rehearsals and publicity announcement of the performances by the Musical Fund society to take place at the Grand Saloon, Washington Hall, including a performance of Beethoven's First Symphony, op. 21.